ïƒ˜ OTONOMI KHUSUS PAPUA SEBUAH UPAYA MERESPON KONFLIK DAN ASPIRASI KEMERDEKAAN PAPUA - MUTAQIN, AZMI (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
The political aspirations of independence is part of the aspirations of the Papuan people and students to function as a democratic civil society which includes the supervision of the course of state policy as stated in his political aspirations associated with the implementation of special autonomy for Papua, Papua stimulate public awareness of the history of politics and political rights, become an alternative channel for people to articulate their political views, given the existing political parties are found to be accommodating to the independence issues that developed in some communities in Papua. Papua Special Autonomy is intended to respond to the Papuan independence movement and nationalism, in essence it has two opposite sides. On one side of the answer calls for independence, to give greater attention to the development of indigenous Papuans, the recognition of Papuan cultural identity, providing big room to do the local authority, but on the other hand can be a kind of institutionalization of the further strengthening of Papuan nationalism, in the meaning of continuing strengthen the spirit of nationalism and ethnic identity of Papua, which may be contra-productive to the aim of strengthening the sentiment of nationalism and Indonesiaan identity. Keyword : autonomy, conflict, freedom